2009
DOI: 10.1016/j.ejphar.2009.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Differential induction of ethanol-metabolizing CYP2E1 and nicotine-metabolizing CYP2B1/2 in rat liver by chronic nicotine treatment and voluntary ethanol intake

Abstract: Alcohol and nicotine are frequently co-used and co-abused, and use of both drugs alone can affect hepatic drug metabolism. We investigated the influences of chronic nicotine treatment and voluntary ethanol intake on the induction of rat hepatic cytochrome P450 (CYP) enzymes that metabolize ethanol and nicotine. Rats were trained to voluntarily drink ethanol (6% v/v, 1 h) with nicotine pretreatment for 10 days. Another group of rats were treated with the same nicotine doses alone. Hepatic CYP2E1, CYP2B1/2 and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…It was previously shown that rats exposed to both ethanol and nicotine had significantly greater levels of hepatic CYP2E1 protein compared with rats exposed to either drug alone (Yue et al, 2009). This enhancement of CYP2E1 protein was partially attributed to a nicotine-stimulated increase in ethanol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that rats exposed to both ethanol and nicotine had significantly greater levels of hepatic CYP2E1 protein compared with rats exposed to either drug alone (Yue et al, 2009). This enhancement of CYP2E1 protein was partially attributed to a nicotine-stimulated increase in ethanol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The induction of CYP2E1 protein in the brain of smoking alcoholics in comparison with nonalcoholic nonsmokers has been proposed [16]. Several studies with experimental animals have shown the induction of CYP2E1 protein and activity in liver and brain by nicotine administration [17][18][19][20]. Furthermore, nicotine treatment increased CYP2E1 protein in a human neuroblastoma cell line [16].…”
Section: Introductionmentioning
confidence: 99%
“…CYP2E1 is increased 1.7, 1.8, and 1.4 fold by the three doses of nicotine alone; CYP2E1 levels are increased by voluntary ethanol intake alone and a further 2.4, 2.2, and 1.8 fold by 0.4, 0.8, and 1.2 mg/kg nicotine respectively versus saline pretreatment (Yue et al 2009 ) . CYP2E1 level correlates with alcohol consumption on day 10 (Yue et al 2009 ) . Chronic nicotine increases voluntary ethanol intake thereby enhancing CYP2E1 level (Yue et al 2009 ) .…”
Section: Rf Tyndale Synergistic Induction Of Cyp2e1 By Ethanol and mentioning
confidence: 97%
“…Nicotine pretreatment of rats increases voluntary ethanol intake on day 10 compared to saline pretreatment (Yue et al 2009 ) . CYP2E1 is increased 1.7, 1.8, and 1.4 fold by the three doses of nicotine alone; CYP2E1 levels are increased by voluntary ethanol intake alone and a further 2.4, 2.2, and 1.8 fold by 0.4, 0.8, and 1.2 mg/kg nicotine respectively versus saline pretreatment (Yue et al 2009 ) .…”
Section: Rf Tyndale Synergistic Induction Of Cyp2e1 By Ethanol and mentioning
confidence: 98%